Comparative appraisal of Cheddar cheese whey and paneer whey for their gross composition, physical properties and chemical characteristics - Parmar, Satishkumar Chaturbhai (Indian Journal of Dairy Science, 2016)
Whey is the major by-product obtained during the manufacture of cheese, casein, paneer and chhana. Fresh samples of Cheddar cheese whey (rennet whey) and paneer whey (acid whey) from a commercial dairy plant were analyzed for gross composition, physical properties and chemical characteristics. The total solids, fat, total protein and lactose content were higher in Cheddar cheese whey (6.82, 0.73, 1.10 and 4.9 %, respectively) than in paneer whey (6.36, 0.58, 0.53 and 4.6 %, respectively). However, the ash (0.45 %) content of paneer whey was higher than Cheddar cheese whey (0.42 %). The average values of specific gravity, viscosity, surface tension, refractive index and electrical conductivity of Cheddar cheese whey were found to be 1.025 at 20 Â°C, 1.27 cp, 49.77 dynes/cm, 1.3427 and 4.21 ms respectively, while, that for paneer whey were 1.020 at 20 Â°C, 1.17 cp, 50.24 dynes/cm, 1.3430 and 4.31 ms respectively. The mean values of pH and titratable acidity of Cheddar cheese whey were found to be 6.7 and 0.12 per cent lactic acid, whereas, that of paneer whey were found to be 5.8 and 0.15 per cent lactic acid respectively. The mean acid degree value of Cheddar cheese and paneer whey were found to be 6.35 and 6.08 milliequivalents of alkali per 100 g of fat, respectively. The study shows that Cheddar cheese whey and paneer whey differed in their composition, physical properties and chemical characteristics.